2004
DOI: 10.1080/09638280412331280352
|View full text |Cite
|
Sign up to set email alerts
|

Research directions in augmentative and alternative communication for preschool children

Abstract: SAL is a viable communication intervention approach for young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…It is important to note that a number of reports addressed the successful use of PECS for young children with autism across the age ranges (Bondy & Frost, 1994;Charlop-Christy, Carpenter, Le, LeBlanc & Kellet, 2002;Lerna, Esposito, Conson, & Massagli, 2014;Stahmer & Ingersoll, 2004;Yoder & Stone, 2006). The evidence also spanned participants with a range of disabilities, from apraxia of speech (Bornman, Alant, & Meiring, 2001) or cerebral palsy (Goossens ' , 1989) to intellectual disability (Sevcik, Romski, & Adamson, 2004;Stephenson, 2007) to dual sensory impairments (Harding, Lindsay, O ' Brien, Dipper, & Wright, 2011;Rowland & Schwiegert, 1989;Schwiegert & Rowland, 1992) to autism (Johnston, Nelson, Evans, & Palazolo, 2003;Nunes & Hanline, 2007).…”
Section: Enhancing Child Communication and Language Developmentmentioning
confidence: 99%
“…It is important to note that a number of reports addressed the successful use of PECS for young children with autism across the age ranges (Bondy & Frost, 1994;Charlop-Christy, Carpenter, Le, LeBlanc & Kellet, 2002;Lerna, Esposito, Conson, & Massagli, 2014;Stahmer & Ingersoll, 2004;Yoder & Stone, 2006). The evidence also spanned participants with a range of disabilities, from apraxia of speech (Bornman, Alant, & Meiring, 2001) or cerebral palsy (Goossens ' , 1989) to intellectual disability (Sevcik, Romski, & Adamson, 2004;Stephenson, 2007) to dual sensory impairments (Harding, Lindsay, O ' Brien, Dipper, & Wright, 2011;Rowland & Schwiegert, 1989;Schwiegert & Rowland, 1992) to autism (Johnston, Nelson, Evans, & Palazolo, 2003;Nunes & Hanline, 2007).…”
Section: Enhancing Child Communication and Language Developmentmentioning
confidence: 99%
“…In our own work, based on detailed speech and language assessment data from a cohort of 4.5 year old children with CP, 75% of participants had clinical speech and / or language impairments [2]. Communication challenges of any kind can lead to educational and social isolation [3], and can have a detrimental impact on nearly all aspects of development [4-6]. Thus, identifying and treating specific speech and language problems at the earliest possible age is of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…All participants increased the number of spontaneous requests during the intervention, half acquired use of PECs earlier and for half there was no difference between acquiring use of the VOCA versus PECS. Sevcik et al [74] also reported positive outcomes following the introduction of a SGD, but with only a general description. Other studies described beneficial effects in a child with apraxia of speech [75]; a 3-year-old with lobar holoprosencephaly [76] and a 17-year-old with multiple disabilities [77].…”
Section: Resultsmentioning
confidence: 99%